2003
DOI: 10.1046/j.1365-2265.2003.01666.x
|View full text |Cite
|
Sign up to set email alerts
|

Tibolone lowers high density lipoprotein cholesterol by increasing hepatic lipase activity but does not impair cholesterol efflux

Abstract: Tibolone lowers HDL-cholesterol in part by increasing hepatic lipase activity. Conservation of sphingomyelin and apoA-II in HDL, as well as cholesteryl ester transfer protein activity, preserves the capacity of plasma to release cholesterol, despite the lower concentrations of HDL-cholesterol. This may have important implications for the use of steroid effects on HDL concentrations as surrogates for atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 50 publications
0
21
0
3
Order By: Relevance
“…Studies after the influence of the common C>T polymorphism in the hepatic lipase gene promoter do not always support this assumption. Several studies have shown that genetically lowered HL activity associated with increased HDL cholesterol is associated with increased rather than decreased CAD risk [6•,8], whereas drug-induced (eg, danazol [23] or tibolone [24]) increased HL activity leading to strongly decreased HDL cholesterol does not necessarily enhance CAD risk.…”
Section: Role Of Hepatic Lipase In High-density Lipoprotein Metabolismmentioning
confidence: 99%
“…Studies after the influence of the common C>T polymorphism in the hepatic lipase gene promoter do not always support this assumption. Several studies have shown that genetically lowered HL activity associated with increased HDL cholesterol is associated with increased rather than decreased CAD risk [6•,8], whereas drug-induced (eg, danazol [23] or tibolone [24]) increased HL activity leading to strongly decreased HDL cholesterol does not necessarily enhance CAD risk.…”
Section: Role Of Hepatic Lipase In High-density Lipoprotein Metabolismmentioning
confidence: 99%
“…For more information about the following terms, which are not mentioned in the text of the present article, see von Eckardstein et al, 27 Borggreve et al, 28 Ma et al, 29 and Cilingiroglu and Ballantyne. 30 ABC A-1: adenosine triphosphate binding cassette, the initiator of cholesterol efflux from the cell membrane.…”
Section: Animal Models: Is Cetp Proatherogenic?mentioning
confidence: 99%
“…The primary action of CETP is to mediate the transfer of cholesteryl esters from HDL to VLDL and LDL in exchange for triglyceride (Figure 2). [27][28][29][30] CETP also promotes the transformation of HDL 2 to HDL 3 , an action that could promote reverse cholesterol transport. CETP inhibition, on the other hand, results in an increase in HDL by markedly delaying catabolism of apoA-I and A-II.…”
mentioning
confidence: 99%
“…the drug with its androgenic properties can reduce high-density lipoprotein cholesterol (HDL-C) as an unfavorable change [25]. However, there are findings that the change of HDL-C is usually transient [33]; on the other hand there are more and more data that we should not focus on HDL-C as it is not main target of the lipid-lowering therapy, also due to the lasting debate on HDL functionality in different patients' groups [42,60,61]. It should be emphasized that data on circulating Lp(a) levels were obtained from studies using different assays for Lp(a).…”
Section: Discussionmentioning
confidence: 95%